7. Software Evaluation Criteria and Terminology - Belyk, Diane; Feist, David (International Review of Research in Open and Distributed Learning, 2002)
This report discusses issues of software selection and terminology, highlighting terms that are useful in evaluation studies. A framework for the evaluation of educational software is presented. Links are cited at the end of this article to the American Society for Training & Development (ASTD), and CNET Network’s glossaries of terminology relating to online collaborative methods.